The value of urinary cysteine rich protein 61 in early diagnosis of contrast-induced nephropathy - XIE Juan; ZHANG Yi-yuan; XU Yong; LI Xiang; Bai Lin; ZHENG Dong-hui (Linchuang shenzangbing zazhi)
Objective To investigate the value of urinary cysteine-rich protein 61（CYR61） in early diagnosis of contrast-induced nephropathy（CIN）. Methods Those patients who were scheduled to have percutaneous coronary intervention（PCI） from January 2017 to August 2018 in Huai’an Hospital Affiliated to Xuzhou Medical University. General clinical data, and those on blood biochemistry, routine test and routine coagulation test were collected. Urine samples were taken before operation, 2 hours, 4 hours and 8 hours after operation. Urinary cysteine rich protein 61（CRY61） level was detected by ELISA. For statistical analysis, based on the preoperative estimated glomerular filtration rate（eGFR）, the patients were divided into two groups: eGFR≥60 mL·min-1·（1.73 m2）-1 group（n=197） and eGFR<60 mL·min-1·（1.73 m2）-1 group（n=50）, and each was divided into CIN subgroup and non-CIN subgroup according to whether the patients had CIN or not. Subgroup analysis was carried out respectively. The value of urine CYR61 in early diagnosis of CIN was evaluated by receiver operating curve（ROC）. Results In the eGFR≥60 mL·min-1·（1.73 m2）-1 group and eGFR<60 mL·min-1·（1.73 m2）-1 group, the urinary CYR61 level of patients with CIN reached its peak at 4 hours after operation, and then decreased. Therefore, the 4-hour postoperative urinary CYR61 was used to diagnose CIN. The ROCs of 4-hour postoperative urinary CYR61 were plotted respectively. The results revealed that, for those patients with eGFR≥60 mL·min-1·（1.73 m2）-1, the optimal cutoff value for CIN diagnosis through the 4-hour postoperative urinary CYR61 was 293.67 ng/L, with sensitivity and specificity of 90.91% and 83.33% respectively, and AUC area under the curve（AUC） of 0.88（95%CI 0.82～0.92）; for those patients with eGFR<60 mL·min-1·（1.73 m2）-1, the cutoff value 266.23 ng/L, with sensitivity and specificity of 100.00% and 78.79%, and AUC of 0.89（95%CI 0.77～0.96）. Conclusions In patients with eGFR≥60 mL·min-1·（1.73 m2）-1 and those with eGFR<60 mL·min-1·（1.73 m2）-1, the 4-hour postoperative urinary CYR61 level can be used as an indicator for early diagnosis of CIN.